PENGARUH EXPRESSIVE WRITING UNTUK MENINGKATKAN SELF DISCLOSURE PADA MAHASISWA PSIKOLOGI UNIVERISTAS NEGERI PADANG - Hilomalo, Rukmana; Maifa Zikra; Afriles Tiara Utami; Muhammad Raihan Okrilyan; Prima Aulia (CAUSALITA : Journal of Psychology, 2024)
Everyone has different self-disclosure abilities, especially individuals who are adapting to a new learning environment, such as students. It's not easy when we open up or talk about ourselves to other people, but when we are reluctant or difficult to tell stories directly, we can put it in written form. One of the skills to improve a person's self-disclosure is expressive writing techniques. This research aims to determine the effect of expressive writing in increasing self-disclosure among Psychology Students at Padang State University. This type of research is experimental research with One Group Pre-test Post-test Design and a quantitative approach. The research population was 27 students from the Department of Psychology, Padang State University, Class K Class of 2022. The research sample consisted of 4 people using purposive sampling technique. Data collection techniques through initial interviews and questionnaires. The data analysis method used is parametric analysis through paired sample T test hypothesis testing via the SPSS (Statistical Product and Service Solution) 25.0 for window application. The research results show that there are differences in the pretest and posttest results where the results of the paired sample T test hypothesis test obtained are 0.019 < 0.05, which shows that expressive writing has an effect on increasing self-disclosure among Psychology Students at Padang State University with a population of Class K students, Class of 2022.